Sensitivity Analysis of Rigid Pavement Design Based on Semi-Empirical Methods: Romanian Case Study - Pleșcan, Costel; Pleșcan, Elena-Loredana; Stanciu, Mariana D.; Botiș, Marius; Taus, Daniel (MDPI AG, 2021)
Due to the intensive process of road construction or rehabilitation of pavement caused by an increase in trafﬁc volume, in the ﬁeld of rigid pavement design and research in Romania, we can say that there is a need to improve the design method. In the last decade, more and more researchers have been concerned about climate change and the increase in trafﬁc volume; hence, there is a need for a renewal of the climatological, as well as trafﬁc, databases because these are part of the input data for the design process. The design method currently used in Romania for jointed plain concrete pavement design is NP081/2002. The limitation of the data and the lack of lifetime estimation of structural and functional performance are the main aspects that need to be addressed in the new design procedure. The Mechanistic–Empirical Pavement Design (MEPDG) method offers the possibility of the design of pavement structures by estimating the structural and functional performances. This paper aims to obtain a comparative study of these two methods for the analysis of the input data collected from the ﬁeld corresponding to the three failure criteria, while the symmetry of the characteristics of the material and their asymmetrical thicknesses are compared, thus contributing to the design of viable and long-lasting pavement structures using a rigid pavement with the speciﬁc characteristics of the mountainous area in northeastern Romania on the national road DN17 Suceava—Vatra Dornei. The novelty of this study consists of the implementation of the mechanistic–empirical method MEPDG instead of the old NP081/2002 method used in Romania.